Percutaneous Management of Enterocutaneous Fistulae and Abscess–Fistula Complexes - Ballard, David H.; Erickson, Abigail E.M.; Ahuja, Chaitanya; Vea, Romulo; Sangster, Guillermo P.; D'Agostino, Horacio B. (Digestive Disease Interventions, 2018)
Abscess–fistula complexes and enterocutaneous fistulae are due to postoperative, spontaneous, and inflammatory etiologies. Conservative, percutaneous, endoscopic, and surgical treatment options are available options. Interventional radiologists have an array of different treatment strategies, often starting with percutaneous drainage of associated intra-abdominal abscesses. This review article details different percutaneous management strategies, focusing on percutaneous catheter strategies for abscess-fistula complexes along with tract closures strategies for enterocutaneous fistulae.
Keywords: abscess–fistula complex; enterocutaneous fistula; percutaneous drainage; fistula tract embolization; Crohn's disease; interventional radiology